Guidance and control for satellite in-orbit-self-assembly proximity operations - Okasha, Mohamed Elsayed Aly Abd Elaziz; Park, Chandeok; Park, Sang-Young (Elsevier Masson SAS, 2015)
In this paper, the autonomous in-orbit-self-assembly of multiple satellites is exploited in close proximity operations. Guidance and control algorithms are developed based on the closed-form analytical solution of relative motion equations that is completely explicit in time in a general Keplerian orbit. The guidance algorithm is based on a modified version of the inbound glideslope transfer that was used in the past for rendezvous and proximity operations of the space shuttle with other vehicles. The control algorithm is based on a discrete multipulse technique that was used to track the guidance trajectory efficiently while avoiding collisions between satellites during maneuvers. These algorithms are general, and can translate each satellite in the assembly in any direction and decelerate while approaching the desired target location in the final assembly configuration. Numerical nonlinear simulations that illustrate the performance and accuracy of the proposed algorithms are performed in a cubic formation assembly.